1979
DOI: 10.1515/zna-1979-0807
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical and Specific Heat Measurements on Tellurium-Halogen Systems

Abstract: Gibbs free energies of reaction in the systems Te-TeX4 (X = Cl, Br, I) were determined from e.m.f. measurements of solid state galvanic cells using silver halides as auxiliary electrolytes. From the temperature dependence of the e.m.f. the standard entropies and enthalpies of formation SO (298.15 K) and AHi° (298.15 K) have been calculated for oc-Tel, Tel 4 , Te 2 Br, TeBr 4 , Te 3 Cl 2 and TeCl 4 . The specific heats of oc-Tel and Te2Br were determined from 1.5 K to 300 K by adiabatic and differential scannin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1979
1979
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…These structural features have been established and confirmed from X-ray [l] and Mossbauer measurements [3,4]. Physical properties of Te,Br that have been measured and reported thus far are electrical conductivity [5], specific heat, Debye temperatures, and electromotive force [2]. A value of 0.6 eV is reported in [6] for the fundamental energy gap.…”
Section: Introductionmentioning
confidence: 66%
See 2 more Smart Citations
“…These structural features have been established and confirmed from X-ray [l] and Mossbauer measurements [3,4]. Physical properties of Te,Br that have been measured and reported thus far are electrical conductivity [5], specific heat, Debye temperatures, and electromotive force [2]. A value of 0.6 eV is reported in [6] for the fundamental energy gap.…”
Section: Introductionmentioning
confidence: 66%
“…From this it is concluded that the electrical conductivity of the isotypic Te2X (X = Br, I, C1) series does not depend on the species of halogen but only on the configuration of the tellurium unit cell [5]. Concerning the physical properties of Te,Br and other subhalides, it is believed that these materials are generally less anisotropic than elemental Te [2].…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Upon charging the Te electrode to 1.5 V vs. Mg/Mg 2+ , an intermediate state between the two charge plateaus of Te, characteristic 3d 3/2 and 3d 5/2 peaks of Te 2+ at 585.8 eV and 574.5 eV were detected. These two peaks imply the formation of metastable tellurium subchlorides, in which partial Te atoms in the Te chain bind with two chlorine atoms axially, like the Te 3 Cl 2 structure [46] . Additional Te 4+ peaks at 587.7 eV and 577.3 eV were also observed, which could come from the oxidation of active Te 2+ species once exposed to air [32] .…”
Section: Resultsmentioning
confidence: 99%
“…These two peaks imply the formation of metastable tellurium subchlorides, in which partial Te atoms in the Te chain bind with two chlorine atoms axially, like the Te 3 Cl 2 structure. [46] Additional Te 4 + peaks at 587.7 eV and 577.3 eV were also observed, which could come from the oxidation of active Te 2 + species once exposed to air. [32] Further charging the Te electrode to 3.1 V vs. Mg/Mg 2 + led to a significant increase in the intensity of Te 4 + peaks.…”
Section: Methodsmentioning
confidence: 95%